A homoscedastic co-integration analysis of Malaysian financial market. (2018) - Mugableh, Mohamed Ibrahim
This article examined long-term relationships and dynamic links between Malaysian equity market and macroeconomic forces, including inflation rates, interest rates, money supply and real economic activity. It employed the vector error correction model and annual time series for the 1977-2015 period. The empirical results show the existence of six co-integrating vectors, implying a long-term relationship between the selected variables. In addition, inflation rates and interest rates were shown to be negatively associated with Malaysian capital market. Money supply and real economic activity were found to be positively related to Malaysian capital market. However, the sample resulted in several observations during the economic and financial crises periods which influence the findings obtained from the regression.